A kiss at midnight ebook - James, Eloisa (Fairy Tales, 2010)
"Eloisa James writes with a captivating blend of charm, style, and grace that never fails to leave the reader sighing and smiling and falling in love." —New York Times bestselling author Julia Quinn "Romance writing does not get much better than this." —People The Cinderella story moves to Regency England—with more than a few twists and turns along the way! With A Kiss at Midnight, the remarkable Eloisa James spins a delicious tale involving a carriage, a godmother, a pair of rats...and a beauty with no interest whatsoever in getting married—and certainly not to a prince! Read A Kiss at Midnight and see why New York Times bestselling author Lisa Kleypas says, "Eloisa James is extraordinary."